Safety and adequacy of percutaneous kidney biopsy performed by nephrology trainees - Vittoria Esposito; Giulia Mazzon; Paola Baiardi; Massimo Torreggiani; Luca Semeraro; Davide Catucci; Marco Colucci; Alice Mariotto; Fabrizio Grosjean; Giacomo Bovio; Ciro Esposito (BMC Nephrology, 2018)
Abstract Background Recently there has been a progressive loss of specialty related skills for nephrologists. Among the skills we find the kidney biopsy that has a central role in diagnosis of renal parenchymal disease. One of the causes might be the belief that the kidney biopsy should be performed only in larger Centers which can rely on the presence of a renal pathologist and on nephrologists with a large experience. This trend may increase in the short term procedural safety but may limit the chance of in training nephrologists to become confident with the technique. Methods We evaluated renal biopsies performed from May 2002 to October 2016 in our Hospital, a mid-sized facility to determine whether the occurrence of complications would be comparable to those reported in literature and whether the increase in the number of biopsy performing physicians including nephrology fellows which took place since January 2012, after our Nephrology Unit became academic, would be associated to an increase of complications or a reduction of diagnostic power of renal biopsies. Three hundred thirty seven biopsies were evaluated. Patients underwent ultrasound guided percutaneous renal biopsy using a 14 G core needle loaded on a biopsy gun. Observation lasted for 24 h, we evaluated hemoglobin levels 6 and 24 h and kidney ultrasound 24 h after the biopsy. Results Complications occurred in 18.7% of patients, of these only 1,2% were major complications. Complications were more common in female (28%) compared to male patients (14,8%) (p = 0.004). We found no correlation between diagnosis, kidney function and complication rates; hypertension was not associated to a higher risk in complications. The increase of biopsy performing personnel was not associated to an increase in complication rates (18,7% both pre and post 2012) or with an increase of major complications (1.2% vs 1,2%). Conclusions Kidney biopsy can be safely performed in mid-sized hospitals. Safety and adequacy are guaranteed even if the procedure is performed by a larger number of less experienced nephrologists as long as under tutor supervision, thus kidney biopsy should become an integral part of a nephrology fellow training allowing more widespread diffusion of this technique.